2015
DOI: 10.1016/j.dcn.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Music training relates to the development of neural mechanisms of selective auditory attention

Abstract: Selective attention decreases trial-to-trial variability in cortical auditory-evoked activity. This effect increases over the course of maturation, potentially reflecting the gradual development of selective attention and inhibitory control. Work in adults indicates that music training may alter the development of this neural response characteristic, especially over brain regions associated with executive control: in adult musicians, attention decreases variability in auditory-evoked responses recorded over pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 76 publications
2
54
1
8
Order By: Relevance
“…Moreover, both musically trained children (Jentschke & Koelsch, 2009) and adults (Fitzroy & Sanders, 2013) are more sensitive to violations of linguistic and music syntax than participants without music training. Perhaps most importantly, recent results also showed that long-term music training positively improves cognitive functions such as auditory attention (Strait, Slater, O'Connell, & Kraus, 2015), visual attention ( Wang, Ossher, & ReuterLorenz, 2015), working and verbal memory (George & Coch, 2011;Ho, Cheung, & Chan, 2003), executive functions (Zuk, Benjamin, Kenyon, & Gaab, 2014;Moreno et al, 2011;Pallesen et al, 2010), and general intelligence (Schellenberg, 2004). These findings are not surprising insofar as playing an instrument at a professional level is a multidimensional task that, together with specific motor abilities, requires acute auditory perception and focused attention, code switching between the visual information on the score and the corresponding sounds, as well as the ability to maintain auditory information in short-and long-term memory.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, both musically trained children (Jentschke & Koelsch, 2009) and adults (Fitzroy & Sanders, 2013) are more sensitive to violations of linguistic and music syntax than participants without music training. Perhaps most importantly, recent results also showed that long-term music training positively improves cognitive functions such as auditory attention (Strait, Slater, O'Connell, & Kraus, 2015), visual attention ( Wang, Ossher, & ReuterLorenz, 2015), working and verbal memory (George & Coch, 2011;Ho, Cheung, & Chan, 2003), executive functions (Zuk, Benjamin, Kenyon, & Gaab, 2014;Moreno et al, 2011;Pallesen et al, 2010), and general intelligence (Schellenberg, 2004). These findings are not surprising insofar as playing an instrument at a professional level is a multidimensional task that, together with specific motor abilities, requires acute auditory perception and focused attention, code switching between the visual information on the score and the corresponding sounds, as well as the ability to maintain auditory information in short-and long-term memory.…”
Section: Introductionmentioning
confidence: 94%
“…The first interpretation, in terms of cascading effects, is that enhanced auditory perception and auditory attention (Strait et al, 2015) in musicians drive the facilitation observed in word learning through different subsequent steps (i.e., building up new phonological representations and attaching meaning to them, storing this new information in short-and long-term memory). In support of this interpretation, the error rate in the musicality test was correlated with the size of the N400 effect in the semantic task in musicians but not in controls (Figure 7), thereby clearly pointing to a relationship between auditory perception/ attention and word learning.…”
Section: Cascading Effects From Perception To Word Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Liking the music is, therefore, one major aspect when seeking positive effects from its listening. Among many other effects, major higher cognitive functions positively affected by music include reading and literacy skills [33], working memory and mathematical abilities [34], memory [35] or concentration and attention [36].…”
Section: The Effects Of Musicmentioning
confidence: 99%
“…A long-term of auditory experience can improve the performance of the whole auditory system. Therefore, a subject who has a good processing of speech sounds has better electrophysiological responses for this type of stimulus, showing that auditory experience might modify the basic sensorial coding of the whole auditory pathway [18][19][20][21]. On the other hand, a subject who has auditory deprivation may have significant electrophysiological changes in the auditory system, as can be seen in children with history of otitis media.…”
mentioning
confidence: 99%